(1347) new urban centers in the rid zones the case of the south region of Egypt مراكز حضرية جديدة في المناطق الريفية بالمنطقة الجنوبية من مصر - bassiouni, mohamed salah (The Institute Of National Planning., 2018)
The arid zones are commanding attention today. The world has begun to realize the vast mineral wealth and the enormous solar energy potential they contain. Many see the arid lands and deserts as the world's last great reservoirs of open space, frontiers that man can farm and make.